Pengaruh Pemberian Dana Kapitasi Dengan Motivasi Kerja Dokter Puskesmas di Wilayah Perkotaan di Indonesia - Rusdiana Rusdiana; Ahmad Fickry Faisya (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The payment of capitation funds affects the motivation and performance of health workers in providing quality services at the Puskesmas. The work motivation of doctors can affect the quality of service and the performance of other health workers. The purpose of this study is to determine the effect of the distribution of capitation funds on the work motivation of doctors in Puskesmas in Indonesia. This study uses secondary data from Risnakes 2017 research results with cross-sectional design. The sample was all doctors in the puskesmas in Indonesia who were successfully interviewed and had independent variables is 4.012 sample. Data analysis was performed descriptively and statistically using chi-square test and logistic regression. From the results of the study found there is a relationship between the suitability of the distribution of capitation funds with the work motivation of doctors in urban health centers in Indonesia with a P value of 0,000 and PR 1,309 (95% CI 1,153 - 1,487). This means that the appropriate distribution and capitation have an influence of 1,309 times in increasing the work motivation of doctors in Indonesian health centers. The distribution of capitation funds must be in accordance with the workload of doctors at the puskesmas to increase motivation and performance of quality services at the puskesmas and the existing regulations must be regularly evaluated.